Proliferation-associated 2G4 P48 is stabilized by malignant T-cell amplified sequence 1 and promotes the proliferation of head and neck squamous cell carcinoma - Legang Sun; Guoyi Xing; Wenlong Wang; Xiangrui Ma; Xiangbin Bu (Elsevier, 2023)
Background/purpose: Proliferation-associated protein 2G4 (PA2G4) has alternative transcriptional and translational initiation. One dominant transcript ENST00000303305 could be translated into two protein isoforms (PA2G4-P42 and PA2G4-P48). In this study, we aimed to explore the effects of PA2G4-P42 and PA2G4-P48 on the proliferation of head and neck squamous cell carcinoma (HNSCC) and the mechanisms regulating PA2G4-P48 stability. Materials and methods: HNSCC cell lines HSC2 and SCC25 with relatively low PA2G4 expression were used for in-vitro cell studies. PA2G4-P42 and PA2G4-P48 overexpression lentiviruses were generated. In vitro cell proliferation was assessed by CCK-8 and colony formation. In vivo tumor cell proliferation was assessed by HSC2 cell-derived xenograft tumors. Liquid chromatography-mass spectrometry (LC-MS)/MS and co-immunoprecipitation (co-IP) assays were applied to check PA2G4-P48 interacting partners. Cycloheximide (CHX) chase and ubiquitin-based co-IP assays were also performed. Results: PA2G4-P48 was the dominant isoform, with substantially higher expression than PA2G4-P42 in HNSCC. PA2G4-P48 overexpression enhanced HNSCC cell proliferation, but PA2G4-P42 overexpression slowed the proliferation. MCTS1 interacted with PA2G4-P48, but not PA2G4-P42. PA2G4 protein but not its mRNA expression was decreased in cells with MCTS1 knockdown. MG132 treatment abrogated this alteration. MCTS1 overexpression significantly elevated the half-life of PA2G4-P48, while its knockdown drastically reduced the half-life compared with the control cells. In addition, MCTS1 overexpression significantly decreased the polyubiquitination of exogenous flag-tagged PA2G4-P48. MCTS1 overexpression-induced cell proliferation was hampered by knocking down of PA2G4-P48. Conclusion: PA2G4-P42 and PA2G4-P48 exert growth-suppressive and growth-promoting effects in HNSCC, respectively. MCTS1 can interact with PA2G4-P48 and prolong its half-life by reducing its poly-ubiquitination.